An Innovative Approach Toward a Comprehensive Distance Education Framework for a Developing Country. Issue 4 (1st October 2016) - Aktaruzzaman, Md; Plunkett, Margaret
ABSTRACT: This article reports on part of a study conducted to collate the policies and practices of two successful distance education providers of the developed world with those of a provider in Bangladesh in order to inform a culturally appropriate distance education framework for a developing country. This article also describes an innovative theoretical model, Adapting Structuration Theory In Distance Education, conceptualized as part of a broader study, to address the underlying issues and to generate propositions for the framework.